2021
DOI: 10.1038/s41438-020-00435-5
|View full text |Cite
|
Sign up to set email alerts
|

Genome and transcriptome of Papaver somniferum Chinese landrace CHM indicates that massive genome expansion contributes to high benzylisoquinoline alkaloid biosynthesis

Abstract: Opium poppy (Papaver somniferum) is a source of morphine, codeine, and semisynthetic derivatives, including oxycodone and naltrexone. Here, we report the de novo assembly and genomic analysis of P. somniferum traditional landrace ‘Chinese Herbal Medicine’. Variations between the 2.62 Gb CHM genome and that of the previously sequenced high noscapine 1 (HN1) variety were also explored. Among 79,668 protein-coding genes, we functionally annotated 88.9%, compared to 68.8% reported in the HN1 genome. Gene family an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 49 publications
3
20
0
Order By: Relevance
“…The first event occurred in the Ranunculales ancestor at around 110 Mya, as previous studies had also suggested (Pabón-Mora et al, 2013;One Thousand Plant Transcriptomes Initiatives, 2019;Pei et al, 2021). After that, we detected another WGD event around 80 Mya after the divergence of Hydrastideae, but before the divergence of…”
Section: Whole Genome Duplicationssupporting
confidence: 67%
“…The first event occurred in the Ranunculales ancestor at around 110 Mya, as previous studies had also suggested (Pabón-Mora et al, 2013;One Thousand Plant Transcriptomes Initiatives, 2019;Pei et al, 2021). After that, we detected another WGD event around 80 Mya after the divergence of Hydrastideae, but before the divergence of…”
Section: Whole Genome Duplicationssupporting
confidence: 67%
“…The number of whole-genome duplications is correlated with gene family size [47,50], which is consistent with our results, since P. somniferum and G. max with two WGD events had the largest sizes of SPX family [51,52]. The expansion of SPX family in these two plants is mostly affected by WGD duplication type, while segmental/local duplication type was the main contributor of expansion in S. moellendorffii, the species with third greatest SPX family, which might explain its unique classes.…”
Section: Evolutionary Conservation and Divergence Of Spx Gene Family From Algae To Legumessupporting
confidence: 92%
“…Additionally, LTR annotation was performed to estimate the assembly genome quality. Compared with Aquilegia oxysepala (16.7) 21 and Aquilegia coerulea (12.6) 22 in the family Ranunculaceae, a high LAI score of 17.86 showed that the assembly of C. chinensis yielded high sequence continuity and met the reference quality 23 . Overall, the assembled C. chinensis genome contains 595.32 Mb (62.13%) of repetitive sequences, most of which are transposable elements (581.03 Mb; 60.63%).…”
Section: Resultsmentioning
confidence: 99%
“…To confirm this, we determined Ks rates between C. chinensis and N. nucifera , finding that the mean Ks was larger than that between M. cordata and N. nucifera . Then, we adjusted the Ks distributions of M. cordata according to the ratio of the Ks value of the orthologous gene pairs between C. chinensis-N. nucifera and M. cordata - N. nucifera according to the method of Paterson et al 26 and Pei et al 22 . The adjusted result showed that C. chinensis , A. coerulea and M. cordata occupied almost the same position, strongly implying that they shared a common WGD event (Fig.…”
Section: Resultsmentioning
confidence: 99%